2019
DOI: 10.18203/2349-2902.isj20195950
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinico-demographic risk factors for postoperative pulmonary complications following gastrointestinal surgery

Abstract: Background: Postoperative pulmonary complications (PPC) are one of the commonest complications following gastrointestinal surgery. They lead to increased mortality, increased length of intensive care unit (ICU) stay, and higher cost of treatment. Identifying the risk factors of PPC helps in predicting its occurrence and to develop preventive measures. The objectives of the present study were to study the clinical and demographic risk factors for PPC following gastrointestinal surgery.Methods: The study was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…e possible explanation for this could be a larger sample size used in their study, and interobserver variability could have the potential to affect the finding. However, this finding was comparable with the results of the observational analytical study conducted in India by Sinouvassan et al which came out with an incidence of 34% [21]. Our study's finding was also in line with a retrospective study conducted in Turkey by Diken et al which showed an incidence of 32.6% [22].…”
Section: Discussionsupporting
confidence: 93%
“…e possible explanation for this could be a larger sample size used in their study, and interobserver variability could have the potential to affect the finding. However, this finding was comparable with the results of the observational analytical study conducted in India by Sinouvassan et al which came out with an incidence of 34% [21]. Our study's finding was also in line with a retrospective study conducted in Turkey by Diken et al which showed an incidence of 32.6% [22].…”
Section: Discussionsupporting
confidence: 93%